2014
DOI: 10.1186/1475-2891-13-41
|View full text |Cite
|
Sign up to set email alerts
|

Validity and relative validity of a novel digital approach for 24-h dietary recall in athletes

Abstract: BackgroundWe developed a digital dietary analysis tool for athletes (DATA) using a modified 24-h recall method and an integrated, customized nutrient database. The purpose of this study was to assess DATA’s validity and relative validity by measuring its agreement with registered dietitians’ (RDs) direct observations (OBSERVATION) and 24-h dietary recall interviews using the USDA 5-step multiple-pass method (INTERVIEW), respectively.MethodsFifty-six athletes (14–20 y) completed DATA and INTERVIEW in randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 25 publications
(35 reference statements)
0
30
0
Order By: Relevance
“…(Item 11); and "Were the subjects recruited over the same time period?" (Item 18) Only two studies [49,54] reported whether an attempt was made to blind those measuring the main outcomes of the intervention (i.e. Item 12) ( Table 5).…”
Section: Evaluation Of Methodological Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…(Item 11); and "Were the subjects recruited over the same time period?" (Item 18) Only two studies [49,54] reported whether an attempt was made to blind those measuring the main outcomes of the intervention (i.e. Item 12) ( Table 5).…”
Section: Evaluation Of Methodological Qualitymentioning
confidence: 99%
“…The current review identified a limited number of studies (n=7) which evaluated the validity of a novel dietary assessment tool or instrument compared to one or more reference method(s) [29,[49][50][51][52][53] and/or a biomarker in an athlete population [50,54]. Peer-reviewed version available at Nutrients 2017, 9, 1313; doi:10.3390/nu9121313 of acceptable validity for group level comparisons [49,51,54], individual agreement was not as strong, especially for athletes with high energy intakes [49,50,54]. A variety of statistical tests were used to assess study validity (e.g.…”
Section: Studies Comparing Dietary Intake By Two or More Methods Of Dmentioning
confidence: 99%
See 3 more Smart Citations